Technological features of piston casting - M. A. Sadokha (Литьë и металлургия)
The results of studies of obtaining complex castings from aluminum alloys using the self-filling method are presented. The influence of a number of technological parameters (pouring time, chill cooling mode, the use of self-filling, etc.) on the quality of the resulting piston castings has been studied. The optimal time for filling the chill mold was determined when casting pistons. It is shown that the chill mold cooling mode has a significant impact on the quality of castings.